Historical development of urban green infrastructure and possibilities of its implementation in the Republic of Croatia - Hrdalo, Ines (Array, 2021)
Research has been motivated by a wide range of concepts of the term urban green infrastructure. As the aim was to indicate a clear basis for the term, an investigation of its development was a necessity, not only in the European, but also in a broader context. Although green infrastructure is included in the 21st century policies of protection and development of EU landscapes, its foundations can be traced back to the models of ideal Renaissance towns and urbanist concepts mainly from the 19th and 20th century. In these historical periods used concepts meant urban landscapes as systems, a part of the environment, as seen in green corridors, green belts, green wedges, green networks and through the perception of urban green systems. As a modern concept the urban green infrastructure has been upgraded with developed roles, extending functions, scopes and scales from previous historical models. In that sense it maintains its social role of improving the quality of life in towns, while at the same time defining town texture with its urban morphological significance. At the same time it also develops ecological values and extends its scale to nonurban local, regional and international contexts.Despite its benefits, spatial planning documents in the Republic of Croatia still lack measures and actions which would recognise the true benefit of green infrastructure in spatial development.